Gender and Fundamentalism in Khaled Hosseini's A Thousand Splendid Suns - Hamzah, Nanda Nabilla (UIN Syarif Hidayatullah Jakarta, 2022)
This paper aims to challenge the reductionist views of Islam and Muslim women in Khaled Hosseini's A Thousand Splendid Suns (2017). In doing so, this paper explores the connection of gender discourse with the Islamic political movement in Hosseini's novel. It also seeks to challenge the gendered bias in the novel by using Amina Wadud's concept of Islamic Feminism. Through the subjugated life of women's characters, the concept of hegemonic masculinity is applied to give an in-depth analysis of gender relations and fundamentalism in the novel. The research focuses on understanding misogynist attempts that marginalized women and legitimized gender inequality. The findings indicate that hegemonic masculinity is unquestionably backed up under the fundamentalist's reign of the Mujahideen and the Taliban with their implementation of Sharia law. Furthermore, the characters have shown dissimilar attitudes in facing the situations. As the main male character, Rasheed is depicted as a manifestation of the misogynistic setting created by both regimes. Meanwhile, the two main female characters show strength, resistance, and resilience in facing the unequal systems. However, while the fundamentalist justifies their action by using Islam as their shield, it is written in the Quran that Islam never discriminates against women but encourages their fundamental rights. Thus, Hosseini's novel complicates the ideas of gender, fundamentalism, and masculinity through the complex relationships of his characters within their families and societies. However, these complex societies do not represent Islam or the Muslim communities as the Muslim world is not only in Afghanistan, but many countries, such as Egypt, Pakistan, and Indonesia, practice Islam in a very different way from those in Afghanistan Hosseini's novel.